First-line manager as change agent : Reducing the resistance to change - Kyttä, Heidi (My University, 2020)
The need to change is important in numerous organizations, as there is need to adapt to the changing markets to stay competitive. The change can be led in organization by change agent who can be organization’s first-line manager. However, the change can be resisted in organi-zation but the resistance to change can be reduced with different methods as change is led. The study’s purpose is to understand how first-line managers as change agents reduce resistance to change as change is led in organization. Existing literature was studied, and empirical research was conducted to meet the purpose of the study. The empirical part of study was executed as single case study approach in organization operating in retail industry by interviewing five first-line managers. The interviews were conducted in March 2020 as semi-structured interviews. The data analysis used thematic analysis to guide analysis of the interview data. The study’s findings propose that first-line managers manage change and reduce resistance by identifying suitable approach for unit where the change is implemented. The findings propose that the first-line managers understand possible reasons for resisting the change and how change is resisted by individuals. Findings also suggest that first-line managers use several competencies when implementing change that can enable them to reduce resistance to change. However, it was identified in the findings that used competencies varied as first-line managers have different strengths. Also, the findings suggest that using suitable leadership method enables to facilitate the change implementation in organization. The study’s findings support mainly prior studies how the resistance to change can reduced. However, findings suggest that first-line managers do not use all possible methods to reduce the resistance to change but select suitable method by considering the unit and the change. Findings enhance the understanding of first-line managers methods to reduce resistance, reasons for resisting the change and methods to facilitate change. Additionally, study’s findings can be used in organization where first-line managers lead change. Still, further research is required to understand the transferability of the study’s findings.

Tarve muuttua on tarpeellista useimmissa yrityksissä, koska niiden on mukauduttava muuttuviin markkinoihin pysyäkseen kilpailukykyisinä. Yrityksessä muutosta johtaa muutosagentti, joka voi olla yrityksen lähiesimies. Muutosta saatetaan kuitenkin vastustaa yrityksessä, mutta muutosvastarintaa voidaan vähentää erilaisilla tavoilla muutosta johtaessa. Tutkielman tarkoituksena on ymmärtää, miten lähiesimiehet muutosagenttina vähentävät muutosvastarintaa johtaessaan muutosta. Tavoitteen saavuttamiseksi tutkielmassa tutkittiin aikaisempia tutkimuksia muutosvastarinnasta ja lähiesimiehistä. Lisäksi tutkielmassa toteutettiin empiirinen tutkimus. Tutkielman empiirinen osa toteutettiin tapaustutkimuksena vähittäiskaupan alan yrityksessä haastattelemalla viittä lähiesimiestä. Haastattelut toteutettiin maaliskuussa 2020 puolistrukturoiduilla haastatteluilla. Haastatteluaineiston analysoinnissa hyödynnettiin temaattista analyysiä. Tutkimuksen tulokset esittävät lähiesimiesten johtavan muutosta ja vähentävän muutosvastarintaa yksikköön sopivalla tavalla. Tuloksissa havaittiin myös lähiesimiesten ymmärtävän mahdollisia syitä muutoksien vastustamiseen ja miten työntekijät vastustavat muutoksia. Tuloksissa huomattiin lähiesimiesten käyttävän useita pätevyyksiä muutostilanteessa, joista voi olla hyötyä muutosvastarinnan vähentämisessä. Tutkielmassa havaittiin pätevyyksien eroavan lähiesimiesten välillä, koska heillä on eri vahvuudet. Lisäksi tuloksissa huomattiin sopivan joh-tamistyylin helpottavan muutoksen käyttöönottoa yrityksessä. Tutkimuksen tulokset tukevat pääosin aikaisempia tutkimuksia, miten muutosvastarintaa voi vähentää yrityksessä. Tuloksissa huomattiin, etteivät lähiesimiehet käytä kaikkia mahdollisia toimia muutosvastarinnan vähentämiseen, vaan lähiesimiehet valitsevat yksikköön ja muutokseen sopivan tavan vähentää muutosvastarintaa. Tulokset lisäävät ymmärrystä lähiesimiehen tavoista vähentää muutosvastarintaa, syitä miksi muutosta vastustetaan ja miten muutosta johdetaan. Lisäksi tutkimuksen tulokset ovat hyödyllisiä yrityksille ja lähiesimiehille, jotka johtavat muutosta yrityksessä. Lisätutkimusta kuitenkin tarvitaan tuloksien yleistettävyyden tutkimiseksi.
Keywords: resistance to change, first-line manager, change, change management